Influences of rurality on small business owner mental well‐being in regional NSW. (12th October 2022) - Simmons, Peter; Dalton, Hazel
Abstract: Objective: To explore the influences of rurality on small business owner mental well‐being and approaches to managing stress and mental well‐being. Design: Semistructured interviews with small businesspeople. Concepts of salutogenesis and pathogenesis were used to interpret rurality influences on business and mental well‐being. A stress‐coping framework was used to categorise approaches to managing mental well‐being. Setting: Central Western New South Wales. Participants: Eleven female and male rural small businesspeople across sectors, including farming, allied health, beauty care and retail businesses. Main Outcome Measures: Interviewee descriptions of experiences of small business and rurality and approaches to managing mental well‐being. Findings: Rurality influenced mental well‐being in four main ways: Business integration with community and owner identity ; Visibility and being known ; Different financial pressures ; and Options for specialised support and casual relief . Rurality can be salutogenic and pathogenic, depending on circumstances, and pressures arising from rurality may differ for 'locals' and recent arrivals. High visibility in a small community can lead to a satisfying sense of belonging and connection. It can also create unwanted feelings of obligation and being watched. Most commonly the interviewees used emotional supports or distraction to adapt to stressors. This may be due to limited options to change or disengage from stressors in rural contexts. Conclusion: Rurality brings its own benefits and challenges to small businesspeople's mental well‐being. Given the immense contributions of small business to rural society and economies, investments in understanding and supporting the mental well‐being of rural small businesspeople should be a high priority for communities and all levels of government.